WA-21-6-A and WB-21-5-A speleothem geochemistry - Paul S Wilcox; Manfred Mudelsee; Christoph Spötl; R Lawrence Edwards (PANGAEA, 2022)
The dataset includes speleothem carbon isotopes, oxygen isotopes, U-Th ages, and fluid inlcusion hydrogen isotopes used to reconstruct climate in southeastern Alaska during the past ~3,500 years. Speleothem WB-21-5-A was collected in Wishbone Cave (55.774 N, -133.191 E; 420 m.a.s.l.) and speleothem WA-21-6-A was collected in Walkabout Cave (55.776° N, 133.195° W; 350 m.a.s.l.) on May 21, 2022 and June 21, 2022, respectfully. The data collection was completed between September 2021-March 2022. U-Th ages were measured on a ThermoFisher Neptune Plus multi-collector inductively coupled plasma mass spectrometer, and stable/fluid inclusion isotopes were measured on a ThermoFisher Delta V isotope ratio mass spectrometer.